Peran Komunikasi Lintas Budaya dalam Mendorong Pariwisata Lokal: Studi Kasus Kota Tanjung Balai - Pasaribu, Jefri Hasian; Suharyanto, Agung (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to examine the role of cross-cultural communication in promoting local tourism in Tanjung Balai City. As a coastal city with ethnic and cultural diversity, Tanjung Balai serves as a dynamic interaction space for local residents, domestic, and international tourists. This study used a qualitative approach with a case study method, through in-depth interviews, observations, and document analysis. The results indicate that cross-cultural communication plays a crucial role in creating shared understanding, improving the quality of tourism services, and strengthening the destination's image. Harmonious cultural interactions can create a more inclusive tourism experience and expand the reach of local tourism promotion. However, challenges such as language differences, cultural stereotypes, and limited communication skills among local residents remain obstacles that need to be addressed. Therefore, a more targeted communication strategy is needed through cross-cultural training, collaboration between the government and tourism actors, and strengthening the role of the community in destination promotion. The findings of this study confirm that cross-cultural communication is a strategic factor that can increase the competitiveness and sustainability of local tourism in Tanjung Balai City.